Peran Pemerintah dalam Menangani Kasus Kekerasan pada Perempuan di Kota Makassar - Kahar Akeb Muzaqar; Ihyani Malik; Dian Lestari (PT. Palem Edukasi Nusantara, 2025)
This research examines the role of the Makassar City Women's Empowerment and Child Protection Office (DPPPA) in handling cases of violence against women using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation and analyzed using triangulation as a data validation technique. This study aims to explore the five main roles of government based on the theory of government roles by Sondang P. Siagian which includes five indicators with the following findings: (1) Stabilizers have been carried out through socialization of the community and the establishment of community shelters, (2) Innovators have been carried out by launching the “Bacce” application, (3) Modernizers are carried out by efforts to increase the internal capacity of DPPPA, (4) Pioneers are carried out by implementing a code of ethics, obligations, and prohibitions of officers, (5) Implementers are carried out by issuing Standard Operating Procedures (SOPs) to become a reference in reporting to case resolution.